The Structure and Elasticity of CaO3 Under High Pressure by First-Principles Simulation - Wang, Hanyu; Liu, Lei; Yang, Longxing; Sun, Fengxia; Yi, Li; Liu, Hong (Frontiers in Earth Science, 2022)
The structure, electrical properties, elasticity and anisotropy of the newly discovered mantle mineral, CaO3, are obtained under 10-50 GPa by first principles simulation to understand its effect on the composition and structure of the mantle transition zone. Crystal structure and phonon frequencies under 0-50 GPa indicate that CaO3 can exist stably under 10-50 GPa. The band gap of CaO3 is 2.32-2.77 under the explored pressure here and indicate its semiconductor property. The Mulliken's population analysis show Ca-O bond is ionic bond and O-O bond is covalent bond and the strength of O-O bond is higher than that of Ca-O bond. The density, bulk and shear modulus of CaO3 increase with increasing pressure. The compressional wave velocity (Vp) and shear wave velocity (Vs) of CaO3 increase with increasing pressure. The seismic wave velocity of CaO3 is smaller than Preliminary Reference Earth Model(PREM) and common mantle transition zone minerals and it is an very especial low seismic wave velocity phase. The anisotropy of Vs and Vp are respectively 36.47%, 26.41%, 23.79%, 18.96% and 18.37%, 13.91%, 12.75% and 10.64% under 15, 25, 35 and 50 GPa. Those anisotropy are larger than the main compositions of the mantle transition zone; so it may be an important source of seismic wave velocity anisotropy in the mantle transition zone. Our results provide the new evidence for understanding the material composition and the source of anisotropy in the mantle transition zone.